Rancang Bangun Aplikasi Market Place “bidibeng.com” Sebagai Peningkatan Pemasaran Digital - Handayani, Tri; Supriati, Supriati; Triyono, Wahyu; Arif, Muhammad (Madani : Indonesian Journal of Civil Society, 2026)
Improving digital marketing is an urgent need for Micro, Small, and Medium Enterprises (MSMEs) fostered by Bengkalis State Polytechnic. These MSMEs often face challenges in expanding their market reach and adopting modern technology for business. This community service focused on the design of a marketplace application that will be integrated with the Teaching Factory Digital Center. The methods used included analyzing the specific needs of the target MSMEs, designing the system architecture, implementing, and testing the application system together with the community service partners. The results of the activity showed that the bidibeng.com marketplace application can function well and is accepted by the target partners. A total of 25 MSMEs successfully onboarded into the system and more than 120 MSME products were successfully uploaded. This application aims to be a centralized platform that facilitates online product promotions and transactions, thereby directly improving digital marketing and the competitiveness of MSMEs. Furthermore, the implementation of this application demonstrates an improvement in the understanding and readiness of SMEs to utilize digital technology for marketing activities. In the future, the marketplace application integrated with the Teaching Factory Digital Center is expected to be further developed with more adaptive features to support the sustainability of SMEs’ digital transformation.